STATISTICAL ANALYSIS OF FUEL CONSUMPTION IN HATCHBACK CARS IN INDONESIA FOR THE YEAR 2024 USING MATLAB - Ginting, Ph.D, Dianta; Sukendar, Sukendar; Hasanudin, Abdul (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
Due to their affordability and compact size, the annual rise in fuel prices has prompted Indonesian consumers to opt for more fuel-efficient vehicles, particularly hatchback models. This study analyzes the key factors influencing fuel consumption in hatchback cars produced in 2024 in Indonesia using statistical analysis with MATLAB. The data analyzed includes technical specifications from various popular hatchback models in the Indonesian market, such as vehicle weight, torque, engine capacity, and engine technology. The analysis results show that vehicle weight has a moderate positive correlation (r = 0.25) with fuel consumption, meaning heavier cars use more fuel than lighter vehicles. In contrast, engine capacity and torque show weak negative correlations with fuel consumption, with correlation values of -0.13 and -0.18, respectively, suggesting that while these factors influence performance, their effect on fuel efficiency is relatively minimal. The findings highlight the critical importance of vehicle weight reduction as a key strategy for improving overall fuel efficiency. Furthermore, this study provides essential insights for consumers to select vehicles that offer a better fuel economy. It also offers valuable guidance for manufacturers looking to design more fuel-efficient and environmentally friendly cars. The potential for vehicle weight reduction to become a primary focus for increasing fuel efficiency in hatchback cars is especially emphasized, offering hope for a more sustainable automotive market in Indonesia